An efficient route to bispecific antibody production using single-reactor mammalian co-culture. Issue 8 (16th November 2016) - Shatz, Whitney; Ng, Domingos; Dutina, George; Wong, Athena W.; Dunshee, Diana Ronai; Sonoda, Junichiro; Shen, Amy; Scheer, Justin M.
ABSTRACT: Bispecific antibodies have shown promise in the clinic as medicines with novel mechanisms of action. Lack of efficient production of bispecific IgGs, however, has limited their rapid advancement. Here, we describe a single-reactor process using mammalian cell co-culture production to efficiently produce a bispecific IgG with 4 distinct polypeptide chains without the need for parallel processing of each half-antibody or additional framework mutations. This method resembles a conventional process, and the quality and yield of the monoclonal antibodies are equal to those produced using parallel processing methods. We demonstrate the application of the approach to diverse bispecific antibodies, and its suitability for production of a tissue specific molecule targeting fibroblast growth factor receptor 1 and klotho β that is being developed for type 2 diabetes and other obesity-linked disorders.